1991
DOI: 10.1083/jcb.112.5.981
|View full text |Cite
|
Sign up to set email alerts
|

A photoreceptor calcium binding protein is recognized by autoantibodies obtained from patients with cancer-associated retinopathy.

Abstract: Abstract. Cancer-associated retinopathy (CAR), a paraneoplastic syndrome, is characterized by the degeneration of retinal photoreceptors under conditions where the tumor and its metastases have not invaded the eye. The retinopathy often is apparent before the diagnosis of cancer and may be associated with autoantibodies that react with specific sites in the retina. We have examined the sera from patients with CAR to further characterize the retinal antigen. Western blot analysis of human retinal proteins revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(98 citation statements)
references
References 40 publications
4
92
0
2
Order By: Relevance
“…The best characterized NCS protein is recoverin, a calcium-myristoyl switch protein in retinal rod cells (68,69) that controls desensitization of rhodopsin (33) by regulating rhodopsin kinase activity (70). Recoverin was also identified as the antigen in cancer-associated retinopathy (71). Other NCS proteins include neurocalcin (72), frequenin (NCS-1) (73), K ϩ channel-interacting proteins (KChIPs) (34), DREAM͞calsenilin (35,36) and hippocalcin (74).…”
Section: Functional Diversity Of Ncs and S100 Proteinsmentioning
confidence: 99%
“…The best characterized NCS protein is recoverin, a calcium-myristoyl switch protein in retinal rod cells (68,69) that controls desensitization of rhodopsin (33) by regulating rhodopsin kinase activity (70). Recoverin was also identified as the antigen in cancer-associated retinopathy (71). Other NCS proteins include neurocalcin (72), frequenin (NCS-1) (73), K ϩ channel-interacting proteins (KChIPs) (34), DREAM͞calsenilin (35,36) and hippocalcin (74).…”
Section: Functional Diversity Of Ncs and S100 Proteinsmentioning
confidence: 99%
“…Thirkill et al (4) reported on the isolation of an autoantibody which reacts strongly the 23-kDa retinal protein, recoverin. This protein is a member of the E-F hand family of calcium-binding proteins involved in the transduction of light by vertebrate photoreceptors and is also identified as an autoantigen in CAR (12,13). It has been reported that this photoreceptor-specific protein is expressed by the tumor in CARpatients (16) and by a human lung cancer cell line (MN-1112), which was established from tumors of small-cell lung carcinoma patients with CAR (17,26).…”
Section: Discussionmentioning
confidence: 99%
“…CAR is associated with epithelial neoplasm, mostly small-cell lung carcinoma and is characterized by the degeneration of retinal photoreceptors (2-1 1). A photoreceptor protein, recoverin, has been recognized as the autoantigen of this disorder (12)(13)(14)(15)(16)(17). It has been reported that CARis usually found before the diagnosis of primary cancer, but there have been some reports that this disorder occurred during the treatment of malignant diseases (9,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanism for paraneoplastic degenerative retinopathy has not been fully elucidated, the presence of peculiar antibodies in patients who suffer from this disease suggests that autoimmunity plays an important pathogenic role in the development of CAR (Thirkill et al, 1989(Thirkill et al, , 1993. Recently, the CAR antigen was identified as a 23 kDa photoreceptor protein, recoverin, from the screening of retinal proteins in CAR patients' sera (Polans et al, 1991;Thirkill et al, 1992). Recoverin is specifically localised in the photoreceptor cells and participates in the recovery phase of visual excitation and in adaptation to background light (Kawamura, 1994).…”
mentioning
confidence: 99%